2021
DOI: 10.3390/life11101051
|View full text |Cite
|
Sign up to set email alerts
|

Natural Selection beyond Life? A Workshop Report

Abstract: Natural selection is commonly seen not just as an explanation for adaptive evolution, but as the inevitable consequence of “heritable variation in fitness among individuals”. Although it remains embedded in biological concepts, such a formalisation makes it tempting to explore whether this precondition may be met not only in life as we know it, but also in other physical systems. This would imply that these systems are subject to natural selection and may perhaps be investigated in a biological framework, wher… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…How to apply these notions to Pan-Evo, which necessarily will contain a wide variety of types of object -molecule, individual, ecosystem, etc -plus the variants within each category, such as isomers of molecules, different species in an ecosystem, or different variants within a species? Dealing with this array of possibilities requires definition and quantification of the units (eg individual) [29,32,33]. One approach to this definition comes from assembly theory; in this theory, each object can be characterized by the assembly index, which is the minimum number of steps needed to construct the object.…”
Section: Information Life and Intelligencementioning
confidence: 99%
“…How to apply these notions to Pan-Evo, which necessarily will contain a wide variety of types of object -molecule, individual, ecosystem, etc -plus the variants within each category, such as isomers of molecules, different species in an ecosystem, or different variants within a species? Dealing with this array of possibilities requires definition and quantification of the units (eg individual) [29,32,33]. One approach to this definition comes from assembly theory; in this theory, each object can be characterized by the assembly index, which is the minimum number of steps needed to construct the object.…”
Section: Information Life and Intelligencementioning
confidence: 99%
“…Vasas et al (2012) discussed this problem and found that the prerequisite for evolvability are chemical reactions networks with multiple viable cores [62]. Although it remains difficult to imagine theoretical autocatalytic sets capable of evolution by natural selection [63], it is assumed here that RNA-based autocatalytic sets have this ability.…”
Section: Autocatalytic Sets-evolution Of Metabolism Without a Genomementioning
confidence: 99%
“…We argue that it is time to begin experimenting with the long-term effects of the prebiotic natural selection processes that may have aided biotic life to emerge by taming the combinatorial chemical explosion. Little research, especially experimental, has been devoted to this problem [ 13 , 18 , 19 , 20 ]. Among the challenges has been the fact that most synthetic experiments have been limited to a week or less in duration [ 21 ] so that apparatuses that can explore longer-term experiments are needed such as that described, for example, by Asche et al [ 22 ].…”
Section: Introductionmentioning
confidence: 99%